The influence of salicylic acid and methyl jasmonate on ripening and stress regulation mechanisms of tropical fruits during cold storage - Mustafa, Maysoun A. (2016)
Postharvest tools have long been developed for minimising postharvest stresses and preserving fruit quality. However, increasing evidence points towards the role of abiotic stress in improving the bioactivity and nutraceutical value of fruits. This study was an investigation into the effects of postharvest stresses on the bioactive content of the tropical fruits carambola (Averrhoa carambola), dragonfruit (Hylocerues sp.) and mangosteen (Garcinia mangostana). The fruits were subjected to stresses induced by cold storage at 6 °C along with exposure to four different levels of one of the stress hormones salicylic acid (0, 0.1, 1, 2 and 5 mM) and methyl jasmonate (0, 0.01, 0.1, 0.2 and 0.5 mM). Physicochemical responses of all three fruits to the postharvest stresses along with changes in the antioxidant activity were assessed throughout the shelf life of the fruits. The goal was to characterise physiological and biochemical associated stress responses of the tropical fruits, and to evaluate the potential of using these stress responses for enhancing fruit quality.